Proximal sensors for monitoring seasonal changes of feeding sites selected by grazing ewes - Serrano, J. (2018)
Montado is a silvo-pastoral ecosystem of the Mediterranean region, a mixed system of trees and grass, where livestock graze. The information about the spatial and temporal variability of pastures constitutes the basis to estimate available feed, a fundamental decision support tool for the farm manager to define the animal stocking or the rotation of the grazed paddocks. In this study, the intrinsic features of high spatial–temporal variability of Mediterranean grazed pastures were assessed with the objective of evaluating the suitability of two proximal sensing techniques (an active optical sensor, AOS and a capacitance probe) for easily monitoring seasonal variability of pasture productivity and quality linked to animal grazing patterns. The correlation between pasture and sensor parameters was consistent between capacitance and pasture productivity (r2 = 0.68, P<0.01; and r2 = 0.87, P<0.01, respectively for green pasture biomass, PB and pasture moisture content, PMC), between NDVI and pasture productivity (r2 = 0.73, P<0.01; and r2 = 0.96, P<0.01, respectively for PB and PMC) and between NDVI and pasture quality (r2 = 0.44, P<0.05; r2 = 0.69, P<0.01; and r2 = 0.78, P<0.01, respectively for ash, crude protein, CP and neutral detergent fibre, NDF). The approach is a promising methodology for assessing seasonal changes in pasture that have values of biomass that range between 2000 and 85,000 kg ha-1 and vegetative sates from de green and leafy to dry. These results can be an important starting point for studies of evaluation and calibration of the optical sensor specifically for pasture quality assessment in different types of biodiverse pastures. This is a key factor for the management of animal grazing intensity and calculation of feed supplementation needs.